Bovine Ephemeral Fever in Asia: Recent Status and Research Gaps - Lee, Fan (Viruses, 2019)
Bovine ephemeral fever is an arthropod-borne viral disease affecting mainly domestic cattle and water buffalo. The etiological agent of this disease is bovine ephemeral fever virus, a member of the genus Ephemerovirus within the family Rhabdoviridae. Bovine ephemeral fever causes economic losses by a sudden drop in milk production in dairy cattle and loss of condition in beef cattle. Although mortality resulting from this disease is usually lower than 1%, it can reach 20% or even higher. Bovine ephemeral fever is distributed across many countries in Asia, Australia, the Middle East, and Africa. Prevention and control of the disease mainly relies on regular vaccination. The impact of bovine ephemeral fever on the cattle industry may be underestimated, and the introduction of bovine ephemeral fever into European countries is possible, similar to the spread of bluetongue virus and Schmallenberg virus. Research on bovine ephemeral fever remains limited and priority of investigation should be given to defining the biological vectors of this disease and identifying virulence determinants.